Canine Mammary Neoplasms - Evaluation of Tumor Microenvironment - Souza, Fernanda Rezende; Raymundo, Djeison Lutier; Albuquerque, Adriana Silva; Simões, Luiz Manoel Souza; Cassali, Geovanni Dantas (Acta Scientiae Veterinariae, 2022)
Background: The tumor microenvironment is an important target of studies in different types of neoplasms. Understanding the role of general components such as immune, vascular and fibroblastic cells has the objective of contributing to prognosis and treatment. The aim of this study was to evaluate the relationship between mast cells and angiogenesis in benign and malignant mammary neoplasms by investigating the role of degranulation and microlocation of mast cells and neoformed vessels in canine mammary neoplasms. Materials, Methods & Results: Mammary glands (n = 122) from 50 female dogs submitted to mastectomy without chemotherapy were evaluated and categorized into 3 groups: control group (n = 46); malignant group (n = 57) and benign group (n = 19). Lymph nodes without changes (n = 59) and with metastases (n = 6) were also evaluated. To evaluate the MCD (mast cell density) and angiogenesis, Toluidine Blue (0.1%) and Gomori’s Trichrome techniques were performed and adapted from previous studies. Photomicrographs of 10 hotspot areas on a 40x objective lens of the mammary glands and lymph nodes were captured to assess MCD and angiogenesis. In the absence of these areas, random fields were captured. For the mammary glands of the malignant and benign groups, 20 fields were analyzed, as the analysis considered the microlocation (peritumoral and intratumoral). Counting was performed manually using ImageJ software version 1.42q by 2 observers. The statistical analysis were performed using SPSS software version 19.0. The most frequent histological type in the malignant group was carcinoma in mixed tumor (68.42%; 39/57) and in the benign group was benign mixed tumor (57.89%; 11/19). Female dogs without breed pattern were more frequently affected represented 70% of the animals and the mean age was 9 years and 8 months ± 3 years and 1 month. The granulated density of mast cells and peritumor vessels was higher in the malignant group (P = 0.03; P = 0.02). There was also a positive correlation between intratumor and total vessel density and mast cell density. There was no significance between the malignant and benign groups in regard with fibrosis density. Discussion: In this study were observed a greater density of blood vessels in malignant group, suggesting the participation of blood vessels for neoplastic proliferation. Furthermore, these vessels were located in the peritumoral region as in previous studies. The positive correlation between MCD and blood vessels was similar to a previous study performed in canine breast carcinomas and breast cancer in women. Regarding microlocation, another study also found higher MCD in the peritumoral region than in the intratumoral region of canine carcinomas. Although there are already studies for this purpose in cases of oral squamous cell carcinoma in humans, we believe this is the first study to investigate the role of mast cell degranulation in mammary neoplasm of bitches. The MCD was not significant among the malignant and benign groups and in the mammary glands of the control group the MCD was higher, as observed by other studies. Future studies should be associated the survival time and the presence of metastases in order to confirm the findings. In view of these findings, we may conclude that a higher density of mast cells is related to a higher density of blood vessels and that these are more abundant in malignant neoplasms, which reinforces the crucial role of angiogenesis in the neoplastic development. Keywords: tumor microenvironment, mammary tumor, mast cells, angiogenesis, bitches.